2017
DOI: 10.1016/j.arthro.2017.04.095
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Term Results of Particulated Juvenile Articular Cartilage Allograft Transplantation to the Knee

Abstract: Objectives: Full-thickness chondral defects of the knee in the young, active patient remain a concerning orthopedic entity given the low capacity for natural regeneration of articular cartilage and limited established treatment options. In the knee, transplantation of particulated juvenile articular cartilage (Zimmer DeNovo NT) has been shown in small studies with only short-term outcomes to have excellent potential. This is the first study that has followed patients greater than 2 years. Methods: All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A follow-up of 25 patients aged 37 ± 11 years reported significant improvement in clinical outcomes as well as histologically indicated repair of hyaline-like cartilage after 24 months 43 . Another mid-term follow-up study showed a progressive improvement in sequential MRIs with 70% achieving complete filling of knee cartilage defects in 26 patients after 4.4 years 44 . Although many cases using particulated articular cartilage have been performed on patients with full-thickness chondral defects, this treatment is limited by the availability of viable articular cartilage.…”
Section: Discussionmentioning
confidence: 94%
“…A follow-up of 25 patients aged 37 ± 11 years reported significant improvement in clinical outcomes as well as histologically indicated repair of hyaline-like cartilage after 24 months 43 . Another mid-term follow-up study showed a progressive improvement in sequential MRIs with 70% achieving complete filling of knee cartilage defects in 26 patients after 4.4 years 44 . Although many cases using particulated articular cartilage have been performed on patients with full-thickness chondral defects, this treatment is limited by the availability of viable articular cartilage.…”
Section: Discussionmentioning
confidence: 94%
“… 2 , 6 , 8 , 11 , 28 , 29 , 34 , 40 Between 2003 and 2013, more than 8700 patients were successfully treated using particulated AC grafts, including in the knee and the ankle, with no reports of graft rejection. 12 , 23 , 24 , 29 , 34 In a 2-year follow-up study, histological analysis of postoperative biopsy specimens from 8 patients showed both hyaline cartilage and fibrocartilage regeneration within the original defect site. 10 Furthermore, a postoperative magnetic resonance imaging (MRI) study demonstrated that human patellar lesions treated with particulated cartilage had progressive tissue regeneration over 2 years, with MRI signals similar to those of hyaline cartilage.…”
mentioning
confidence: 99%